Evaluation of transurethal alprostadil for safety and efficacy in men with erectile dysfunction - Apichat Kongkanand (2018)
A multicenter study conducted in 5 trial centers, for the safety and efficacy of transurethral alprostadil (Pellet) in 90 subjects. The end results show quite good and the product was satisfactory and safe for all ages. Although there are multiple side effects that seemed to discourage the participants and caused them to dropout, MUSE does work but needs good understanding of the use of the device. MUSE is another alternatives for those who unable to use oral medication or those who require immediate action but need some dexterity.